Lessons Learnt: Index Insurance for the Agricultural Sector in Central America: Honduras - CGIAR Research Program on Climate Change, Agriculture and Food Security (2018)
As part of an engagement between the International Research Institute for Climate and Society of Columbia University (IRI), the CGIAR Research Program on Climate Change, Agriculture & Food Security (CCAFS), Zamorano Agricultural University and the Ministry of Agriculture and Fisheries (SAG), the Index insurance for the agricultural sector in Central America project is a collaborative effort for identifying and implementing producer-driven, development-focused processes for generating climate risk solutions. Many farmers have opportunities to take productive risks, such as taking a loan to buy higher quality seeds. However, the risk of failed crops can prevent them from investing in new technologies. Working with these farmers, project stakeholders identified index insurance as the tool that could present marginalized farmers with the opportunity to transfer enough risk for them to take productive chances. Through participatory processes, the IRI has been able to connect the science, the experts on-the ground and the producers’ experiences to design a drought index insurance product that is in line with the end-users’ needs, while providing insurance companies with new market opportunities.